Lesson Learned from Successful Agricultural Social Entrepreneurship in Guangxi - Zhong, Yu; Thansuwansni, Kittirat; Teekasap, Sombat; Sarawong, Nukul (Journal of Information Technology and Innovation, 2023)
Rural revitalization and young people returning home to start businesses are two major problems facing China. Farmers’ cooperative is one of the main forms of agricultural social entrepreneurship in China, but in practice, the lack of entrepreneurial ability and the lack of market, economic and human resources support have affected the enthusiasm of young people. In this paper, expert surveys, interviews and other methods are used to find out the factors that affect the success of agricultural social entrepreneurship, draw lessons from them, and draw strategies to improve young people’s ability to participate in rural social entrepreneurship. It is clear that the orientation of social entrepreneurship should be adhered to in the process of starting a business. Entrepreneurs can improve their entrepreneurial competence through internal and external learning, market research and social support. The application of technology and management knowledge can improve efficiency and create a good social reputation. Most of the human resources support comes from the support of local communities and experts. The business model of "Company + Cooperative + Farmer" is basically conducive to the development of rural social entrepreneurship.